Butterfly (lepidoptera: rhophalocera) diversity in Bukit Soga, the green lung of Batu Pahat, Malaysia - Abdul Rahman, Aqilah Awg; Mohamed, Maryati; Linatoc, Alona Cuevas (2018)
To accommodate for increase in human population, development of cities and urban areas is necessary. This call for changes in land use. The transition from natural to build environment has affected the natural landscape in many ways; one of which is pollution. Consequently, the native biodiversity within the urban landscape is stressed to maintain an optimum level of ecosystem service in order to sustain ecological integrity. This is where the urban green lung plays its role; to provide for carbon sequestration, oxygen generation, acting as filters to noise and dust, and offers aesthetical values. The study area, Bukit Soga Perdana Recreational Forest is a well–known green lung of Batu Pahat, Johor; the second largest industrial town in Johor. This paper aims to study the biodiversity of butterflies in Bukit Soga and discusses its impact on the urban ecological landscape. Species abundance and habitat characterization based on plant nativity, canopy and vegetation coverage, and disturbance type analysis such as human pressure, were studied. Collection resulted in 43 species of butterflies. Total abundance was 88 individuals, sampled throughout Dec to June 2017. Majority are primary forest species that requires adequate canopy coverage. As for plants, in Bukit Soga most are native with exception to the herbs garden. Surprisingly, habitat disturbance such as human movement does not affect the spatial distribution of primary or secondary forest butterfly species. However, their distribution is largely affected by canopy coverage, as it should be. This suggests that despite the growing recreational activities in Bukit Soga, this urban green lung still play an important role in maintaining the ecological integrity in Batu Pahat.